Sexual Transgression for Power and Identity: A Glimpse on Shakespeare’s Twelfth Night - Sharma, Radha Devi (Crossing the Border: International Journal of Interdisciplinary Studies, 2015)
Crossing social restrictions for identity and status is often the act of dissatisfying group in every society. Shakespearean society which was basically patriarchal and male-dominate set strict restrictions to impose on women’s sphere. However, the suppressed women’s voice sometimes denied the social restrictions in different ways as cross-dressing going beyond the boundary of women’s sexuality. Cross-dressing as sexual transgression was often committed in the actual life of English Renaissance and also in the literary world for independent identity, power and authority. In this regard, this article tries to explore on the sexual transgression committed by the main female character, Viola in the play Twelfth Night to get identity and fulfill her inner desire challenging the socially prescribed norms of gender and sexuality. Crossing the Border: International Journal of Interdisciplinary Studies Vol.3(1) 2015: 71-80